Interview: THE CLUJ MODERN CONTEMPORARY MUSIC FESTIVAL ANALYZED BY ITS ORGANIZER, PH.D. PROFESSOR ADRIAN POP - NEDELCUŢ, Nelida (Studia Universitatis Babes-Bolyai Musica, 2017)
The Cluj Modern festival represents a landmark in Romanian cultural life; getting accustomed to and understanding modern music are the main goals of the event. Even though the promotion of contemporary music is the pursuit of other national festivals as well, in the seasons of philharmonics and opera houses which perform this type of repertoire, the festival receives laudatory reviews from specialists due to its good organization and remarkable artistic level in performance and composition. The editions of the Cluj Modern Festival succeed one another every two years, and the organizers are always trying to offer memorable, meaningful programmes, which represent milestones in Romanian music. The 2017 edition proved to be a success, confirming one of the most important events in the promotion of contemporary Romanian music, while the public in Cluj seems to be more receptive to this type of music than in other parts of the country. Professor and composer Adrian Pop, who has dedicated himself to the organization of the festival since its ninth edition in 2009, has shared with us a few defining details about the organization of this year’s edition of the Cluj Modern Festival, the problems that he faced during the history of the event, as well as suggestions and strategies for the promotion and organization of future editions.